HIV skin manifestations in children. - Maccabruni, A.; Bellosta, M.; Caselli, D.; Domaneschi, E.; Bossi, G. (European Journal of Pediatric Dermatology, 2018)
Since 1980 117 HIV seropositive children were studied in the Departments of Infectious Diseases, Dermatology and Pediatrics of Pavia University (Italy). The mucous and cutaneous manifestations of these children are here reported. According to their own observations and the data of the relevant international literature, the Authors discuss the possible relationship between the staging of the basic disease and the clinical features and course of the most frequent dermatological disorders.